2022
DOI: 10.3390/pharmaceutics15010034
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity and ADMET Analysis of Quinoline-1,4-quinone Hybrids

Abstract: Lipophilicity is one of the basic properties of a potential drug determining its solubility in non-polar solvents and, consequently, its ability to passively penetrate the cell membrane, as well as the occurrence of various pharmacokinetic processes, including adsorption, distribution, metabolism, excretion, and toxicity (ADMET). Heterocyclic compounds containing a nitrogen atom play a significant role in the search for new drugs. In this study, lipophilicity as well as other physicochemical, pharmacokinetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The results of these studies are included in Table 1 , and the graphical visualization of the calculated logP values of each compound is shown in Figure 3 and Figure 4 . Such large differences in the obtained values of the lipophilicity parameter were reported before [ 27 , 28 , 29 ] and, as in these previous studies, accurate experimental measurments are needed in order to narrow them down.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The results of these studies are included in Table 1 , and the graphical visualization of the calculated logP values of each compound is shown in Figure 3 and Figure 4 . Such large differences in the obtained values of the lipophilicity parameter were reported before [ 27 , 28 , 29 ] and, as in these previous studies, accurate experimental measurments are needed in order to narrow them down.…”
Section: Discussionmentioning
confidence: 65%
“…It can be concluded that the group of 10-substituted 1,9-diazaphenothiazines is moderately lipophilic compared to the isomeric 1,6-, 1,8-, 2,7 and 3,6-diazaphenothiazines [ 29 , 30 , 31 , 32 , 33 ]. A comparative summary of selected derivatives with the following substituents, hydrogen atom ( A derivatives), allyl ( B derivatives), propargyl ( C derivatives) and dimethylaminopropyl ( D derivatives), is presented in Table 9 and visualized graphically in Figure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Among other separation techniques, micellar liquid chromatography (MLC) or micellar electrokinetic chromatography (MEEKC), respectively, in which the mobile phase comprises surfactants that allow better mapping of penetration of molecules through biomembranes can be also be used for lipophilicity determination [ 7 ]. The literature review shows that numerous publications have dealt with the subject of determining the lipophilicity of various bioactive compounds using chromatographic methods [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The measure of similarity of two compounds is the Euclidean distance (ED). If the ED distance is similar, it means that the compounds exhibit similar features [63][64][65][66]. As seen in Table S2, the derivatives in different subclusters have the same ED distance, which means that the compounds show high similarity.…”
Section: Discussionmentioning
confidence: 98%